(untitled) (Research, Society and Development, 2021)
The Southern Caracara is a bird of prey, of the family Falconidae, inhabits all the Brazilian territory, they are omnivorous birds adapted for hunting. The digestive system of the predators presents differences in their morphology due to their eating habits. Knowing the importance of the gastrointestinal system, this study aims to carry out a histological study of the tongue, esophagus and the crop of Polyborus plancus. For this purpose, eight avian of both sexes, with different body weights and ages were used, they were euthanized and the organs were collected, fixed, dehydrated and stained with hematoxylin-eosin. It was noted that the tongue has stratified squamous epithelium with mucous glands and with different degrees of keratinization. The esophagus and crop have four well developed muscle layers and mucous glands. Additionally, in the crop there is presence of an adventitious layer that consists of loose connective tissue. We conclude that the tongue, the esophagus and the crop of the Southern Caracara have similar histological organization of several birds like the Pekin Ducks, ostriches, domestic chicken and partridges.